The Value of Difference: Kantian Hospitality and Flikschuh’s Rethinking of Nomadic Encounters - Rajiva, Suma (Con-Textos Kantianos. International Journal of Philosophy, 2017)
In this essay I discuss the issue of Kantian hospitality and how Katrin Flikschuh’s arguments in “Kant’s Nomads: Encountering Strangers” offer us a framework for dealing with certain problems that seem to arise out of the Kantian account, namely, problems of dealing with cultures unlike modern liberal states, such as nomadic and indigenous communities. I look at some criticisms of Kant’s position on hospitality and cosmopolitan right and on how Flikschuh’s discussion helps to resolve these criticisms. I focus especially on her discussion of respectful interaction and openness in the course of encountering cultural others, encounters that inherently and positively contain a large element of unexpectedness.
Keywords: Kant; Flikschuh; hospitality; cosmopolitan right; nomads; respect; difference